Start-ups in the era of digital revolution: factors that shape the intention to launch a new one / Soheyb Kahlessenane, Jauriyah Shamsuddin and Mohd Sobri Minai - Kahlessenane, Soheyb; Shamsuddin, Jauriyah; Minai, Mohd Sobri (Faculty of Business and Management, 2023)
Although we are in the heart of the digital revolution era, the original understanding of "startup" as an enterprise in the early stage still dominated the literature. The vague understanding of the startup concept led to a considerable misunderstanding, which may be misleading in exploring the launching phenomena. Despite this, fewer studies have addressed this issue and accurately understood it from conceptual or empirical perspectives. This paper aims to illustrate the definition of a start-up. After that, the authors utilised secondary data from the existing academic literature to develop a conceptual framework to understand individual and environmental factors' roles in the intention to launch a new start-up and suggest propositions for a future empirical test. The findings identified individual factors (entrepreneurial ideas, skills) that have remained unclear in the literature. Entrepreneurial ideas and skills can be fundamental in pushing individuals to be entrepreneurs. Moreover, university business incubators might introduce as a moderator; the arguments about their effect on personal and intellectual abilities remain unexplored very well. More inclusive conceptual perspectives are required to provide evidence crucial for developing and filling the existing gap. Based on the proposed framework, the authors encourage scholars to test its propositions empirically.